RAPID NONDESTRUCTIVE MECHANICAL STRESS CONTROL - O.V. Nabokova (National Technical University "Kharkiv Polytechnic Institute", 2013)
The paper considers problems of nondestructive mechanical stress control device design. An analytical expression for calculation of EMF induced in the measuring winding of a converter is obtained. The automatic control system developed linearizes the converter output voltage versus mechanical intensity.